Interaction between Chinese Family Business and Cultural Differences in Malaysia - Iskandar Hasan Tan Abdullah; Muhammad Syahmizan Azmi; Sakinah Mat Zin; Lim Soo Chee; Nur Azuki Yusuff (2014)
Family business inheritance among the Chinese community is a tradition that is known by the business community worldwide. Thus, a family business among the Chinese community in Malaysia is common. In fact, the inheritance of this business provides a unique and exciting dimension to be investigated. The paper explores the empirical evaluation on the influence of family business inheritance among the Chinese; who managed to overcome obstacles and conflicts through discussions and negotiations. Using a correlation test to examine the effect of inheritance in a family business among the Chinese, the study stress on the variables such as power distance, uncertainty avoidance, and masculinity vs. femininity, individualism vs. collectivism, time orientation and impact on value dimension. In addition, factor analysis and regression testing are also used to determine the main determinant factor in the family business inheritance among the Chinese community. Primary data were collected from August to October 2011 using questionnaires. Meanwhile, secondary data were gathered through library research and interviews with Chinese traders on the East Coast of Malaysia. From the qualitative study, it is found that the main reasons for refusal to inherit the family business among the younger Chinese generation is due to jobs that offer the lucrative wages as compared to profits earned in the family business. Job status, educational level and age are also the factors that influence the younger Chinese generation not to inherit the family business